COMPARATIVE STUDY OF BRUGGEMAN FACTORS AS A DIELECTRIC PARAMETERS OF ETHANOL, METHANOL AND PROPANOL WITH DIAZEPAM USING TIME DOMAIN REFLECTOMETRY - A.K., DONGARE; S.B., SAYYAD (Innovare Journal of Sciences, 2020)
Objective: The dielectric relaxation study of binary mixture at different concentration and different temperature has been carried out using time domain reflectometry technique in the frequency range of 10MHz to 50MHz. Materials and Methods: Ethanol, Methanol and Propanol with Diazepam used as a binary mixture for the dielectric relaxation study. Results: The dielectric parameters have been determined. The Bruggeman model has been fitted to the dielectric data of mixture. Conclusion: It is concluded that fB shows a small deviation to upper side from the ideal Bruggeman behavior in Ethanol and Propanol and lower side in Methanol with Diazepam binary mixture.